Low annual frequency of HbA1c testing in people with Type 2 diabetes in primary care practices in Germany. Issue 2 (13th December 2017) - Kostev, K.; Jacob, L.; Lucas, A.; Rathmann, W.
Abstract: Aims: To analyse the annual frequency of HbA1c testing, as well as the factors associated with higher or lower testing frequency, in people with Type 2 diabetes mellitus in general practices and specialist diabetes practices in Germany. Methods: A total of 43 509 people diagnosed with Type 2 diabetes between January 2016 and December 2016 in 557 medical practices (51% of all practices) were included in this study. The primary outcome was the annual recorded frequency of HbA1c testing in 2016. Multivariable logistic regression analyses were performed to identify variables associated with the odds of HbA1c concentration being tested at least twice in 2016, using predefined demographic and clinical variables. Results: The mean (sd ) number of reported HbA1c tests was 2.7 (1.6) in 2016. Overall, 74% of individuals had at least two annual HbA1c measurements. The likelihood of receiving ≥2 HbA1c tests was inversely associated with stroke (odds ratio 0.81, 95% CI 0.74–0.89), shorter diabetes duration (≤1 year: odds ratio 0.77, 95% CI 0.70–0.84) and higher mean HbA1c concentration (≥8.5%: odds ratio 0.85, 95% CI 0.76–0.94) and was positively associated with specialist diabetes care (odds ratio 1.24, 95% CI 1.14–1.36), hypertension (odds ratio 1.10, 95% CI 1.04–1.17), hyperlipidaemia (odds ratio 1.48, 95% CI 1.41 to 1.55), renal complications (odds ratio 1.41, 95% CI 1.32 to 1.50), neuropathy (odds ratio 1.27, CI 1.20 to 1.35) and retinopathy (odds ratio 1.38, 95% CI 1.25 to 1.52). Conclusions: Only three out of four individuals with Type 2 diabetes underwent at least two HbA1c tests in Germany in 2016, which means that 25% of individuals underwent fewer tests than required by German guidelines. What's new?: In this study we used a nationwide real‐world database, allowing unbiased estimation of the monitoring frequency of HbA1c in German primary care practices. A total of 75% of individuals with Type 2 diabetes underwent at least two HbA1c tests in Germany in 2016, which means that 25% of individuals received fewer tests than required by German guidelines. The likelihood of having ≥2 HbA1c tests was negatively associated with stroke and positively associated with specialist diabetes care, longer diabetes duration, lower mean HbA1c values, hypertension, hyperlipidaemia, renal complications, neuropathy and retinopathy.